Ethics of ecology and environment - Subbarao, S. (New Delhi Rajat Publications, 2001)
The newly emerging concept of ecology and environment has moved in to the mainstream of public life as a major national and international concern. This provides important opportunities for environmental sociologists to contribute to the understanding and solution of these problems.
Keywords: Environmental ethics; Ecology--Moral and ethical aspects; Geography